THE INFLUENCE OF THE ENVIRONMENTAL ECOLOGICAL HYGIENIC AND MEDICAL SOCIAL FACTORS UPON CHILDREN’S AND TEENAGERS’ HEALTH IN THE DIFFERENT AREAS OF THE REPUBLIC OF DAGESTAN - O. R. Osmanov; R. K.-A. Immiev (Юг России: экология, развитие)
The analysis of the materials by a complex hygienic estimation of the environment of the Republic of Dagestan showed that: – as a whole in the Republic of Dagestan the adverse potential of the atmospheric self-cleaning and the level of the atmospheric air pollution with a dust, sulphur dioxide, carbon monoxide and nitrogen dioxide is observed.